The Chinese Hukou System: Reforming Institutions of Inequality Between the Need for Roots and the Demands of Change - Raimondo, Giulia (Revue québécoise de droit international / Quebec Journal of International Law / Revista quebequense de derecho internacional, 2019)
Since 1978, economic reform and opening-up in the People’s Republic of China have dramatically reoriented the previous planned economy towards the free market, generating an increasingly dynamic economy. The exodus of the rural labour force from the countryside to the industries of the cities significantly sustained the process of industrialization and economic reform. The rapid economic growth did not, however, coincide with appropriate social developments and has not yet led to a commensurate recognition and extension of socio-economic, civil and political rights. This dichotomy is reflected in the maintenance of the hukou (household registration) system, which limits the mobility of the population discriminating between citizens depending on their hukou status. This contribution will explore the evolution of the Chinese hukou system and its human rights implications. It will consider China’s human rights approach in relation to the management of internal migration and the recent proposals to reform the hukou system. Specific human rights concerns will be underscored with regard to the right of freedom of movement and residence within the territory of a State, which is inexorably intertwined with many other fundamental human rights. Unearthing the far-reaching and transversal human rights impact of the hukou system will unveil the overarching principle of equality and non-discrimination as the ultimate benchmark of protection for Chinese internal migrants. A holistic human rights approach to the recently propounded institutional changes is crucial to uphold China’s economic and social stability as well as to better safeguard its founding principle of equality.